Psikodrama Wayang: Menurunkan Toxic Masculinity dan Prevensi Kekerasan terhadap Perempuan - Farahdiba Ramadhani Hakim; Reihan Nisha Gunawan; Siti Zulicha; Abror Hilman; Anisa Fitriani (Journal of Innovative and Creativity, 2025)
Toxic masculinity is one of the factors causing women to become the majority of victims of violence. This tendency encourages men to show inappropriate sides of masculinity due to lack of space for expression. Wayang Psychodrama, a new innovation, designed to reduce toxic masculinity. This research used an experimental method with a pretest-posttest control group design. There were 19 male subjects aged 14-18 years, moderate to high levels of toxic masculinity, divided into experimental and control. The results showed that there was a significant decrease in toxic masculinity scores in the experimental group. Meanwhile, the control group did not experience a significant decrease in scores. The results show that Wayang Psychodrama can reduce toxic masculinity. Moreover, there were a change in mindset based on the seven aspects of The Man Box scale and encouraging changes in mindset related to preventing violence against women, increasing self-confidence, self-expression and emotional control.